The effect Thickness In2O3 film on optical properties (Journal of the College of Basic Education, 2022)
In this work, effect films thickness (106-200-350-500nm) of In2O3 deposited on glass substrates by rapid thermal oxidation at different a range of oxidation temperature up to (350-400-450C°) on , The optical properties .The optical properties show an increasing in transmission characteristics up to 95% at the visible regions (400-700nm) for film thickness 500nm at oxidation temperature 450C° The stud shows that the direct energy band gap have been increased with increasing the film thickness from (3.63-3.41eV)for indirect with increased thickness from (2.65-2.25eV). The calculations have also included some optical constants such as transmittance, absorption coefficient and refractive index.